Context and content of teaching conversations: exploring how to promote sharing of innovative teaching knowledge between science faculty - A. Kelly Lane; Brittnee Earl; Stephanie Feola; Jennifer E. Lewis; Jacob D. McAlpin; Karl Mertens; Susan E. Shadle; John Skvoretz; John P. Ziker; Marilyne Stains; Brian A. Couch; Luanna B. Prevost (SpringerOpen, 2022)
Abstract Background Change strategies may leverage interpersonal relationships and conversations to spread teaching innovations among science faculty. Knowledge sharing refers to the process by which individuals transfer information and thereby spread innovative ideas within an organization. We use knowledge sharing as a lens for identifying factors that encourage productive teaching-related conversations between individuals, characterizing the context and content of these discussions, and understanding how peer interactions may shape instructional practices. In this study, we interview 19 science faculty using innovative teaching practices about the teaching-focused conversations they have with different discussion partners. Results This qualitative study describes characteristics of the relationship between discussion partners, what they discuss with respect to teaching, the amount of help-seeking that occurs, and the perceived impacts of these conversations on their teaching. We highlight the role of office location and course overlap in bringing faculty together and characterize the range of topics they discuss, such as course delivery and teaching strategies. We note the tendency of faculty to seek out partners with relevant expertise and describe how faculty perceive their discussion partners to influence their instructional practices and personal affect. Finally, we elaborate on how these themes vary depending on the relationship between discussion partners. Conclusions The knowledge sharing framework provides a useful lens for investigating how various factors affect faculty conversations around teaching. Building on this framework, our results lead us to propose two hypotheses for how to promote sharing teaching knowledge among faculty, thereby identifying productive directions for further systematic inquiry. In particular, we propose that productive teaching conversations might be cultivated by fostering collaborative teaching partnerships and developing departmental structures to facilitate sharing of teaching expertise. We further suggest that social network theories and other examinations of faculty behavior can be useful approaches for researching the mechanisms that drive teaching reform.